Risk Factors and Management of Catheter Malfunction During Urgent-Start Peritoneal Dialysis - Zhao, Lijuan; Yang, Jun; Bai, Ming; Dong, Fanfan; Sun, Shiren; Xu, Guoshuang (Frontiers in Medicine, 2021)
Background: Catheter malfunction is a common complication of peritoneal dialysis (PD). This study aimed to retrospectively analyze the risk factors and management of catheter malfunction in urgent-start PD. Methods: Patients who underwent urgent-start PD were divided into catheter-malfunction and control groups. Baseline demographic and laboratory data of the two groups were compared, and the risk factors for catheter malfunction were analyzed. Primary outcome measure was catheter survival, and the secondary outcomes were surgical complications and malfunction treatment. Results: Total of 700 patients was analyzed, among whom 143 (20.4%) experienced catheter malfunctions, specifically catheter migration (96, 67.1%), omental wrapping (36, 25.2%), and migration plus omental wrapping (11, 7.7%). Catheter survival time in the malfunction group (202.5 ± 479.4 days) was significantly shorter than that in the control group (1295.3 ± 637.0 days) (P < 0.001). Multivariate analysis revealed higher body mass index [hazard ratio (HR), 1.061; 95% confidence intervals (CI), 1.010–1.115; P = 0.018], lower surgeon count (HR, 1.083; 95% CI, 1.032–1.136; P = 0.001), and higher serum potassium (HR, 1.231; 95% CI, 1.041–1.494; P = 0.036) as independent risk factors for catheter malfunction, while older age (HR, 0.976, 95% CI, 0.962–0.991; P = 0.002) and colonic dialysis (HR, 0.384; 95% CI, 0.254–0.581; P < 0.001) as protective factors. Further subgroup analysis revealed a shorter catheter survival time in patients with younger age ( ≤ 40 years), higher serum potassium levels (≥5 mmol/L), while a longer catheter survival time in patients with colonic dialysis. PD tube and subcutaneous tunnel preservation was successful in 41 out of 44 patients with omental wrapping. All patients had good post-incision prognoses. Conclusions: Urgent-start PD is safe and effective for unplanned PD patients. Adequate pre-operative colonic dialysis and serum potassium level control are conducive in preventing catheter malfunction. Conservative treatment is effective in managing catheter migration alone, while preservation of the PD tube and the subcutaneous tunnel is effective for omental wrapping.